1
$\begingroup$

I am being asked to find the sum of the following convergent series :

$$\sum_{n=0}^∞ \frac{2^n}{6^n} + \frac{3^n}{6^n}$$

Attempting to generalize from partial sums yields nothing of interest:

$s_1 = \frac{5}{6}$

$s_2 = \frac{5}{6} + \frac{13}{36} = \frac{43}{36}$

$s_3 = \frac{43}{36} + \frac{35}{216} = \frac{293}{216}$

$s_4 = \frac{293}{216} + \frac{97}{1296} = \frac{1855}{1296} $

I do not see a pattern here...

How must I proceed to find the sum of this series?

$\endgroup$
  • 3
    $\begingroup$ Do you know $\sum_{n=0}^{+\infty}q^n$ if $|q|<1$ ? $\endgroup$ – C. Dubussy Apr 21 '16 at 20:41
  • $\begingroup$ Why did you repost the question? $\endgroup$ – Vim Nov 28 '16 at 5:30
4
$\begingroup$

It is just the sum of two geometric series in disguise.

$$ \begin{aligned} \underset{i=0}{\overset{\infty}{\sum}}\frac{2^{n}+3^{n}}{6^{n}}&=\underset{i=0}{\overset{\infty}{\sum}}\frac{2^{n}}{6^{n}}+\frac{3^{n}}{6^{n}}\\ &=\underset{i=0}{\overset{\infty}{\sum}}(1/3)^{n}+\underset{i=0}{\overset{\infty}{\sum}}(1/2)^{n}\\ &=\frac{1}{1-\frac{1}{3}}+\frac{1}{1-\frac{1}{2}}\\ &=\frac{3}{2}+2\\ &=\frac{7}{2}. \end{aligned} $$

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ Had the same thought, just to verify I tried it on Wolfram and it gives 3/2. Any idea why? $\endgroup$ – MathematicianByMistake Apr 21 '16 at 20:47
  • 2
    $\begingroup$ It gives 3.5 which is 7/2 @MathematicianByMistake $\endgroup$ – Eric Johnson Apr 21 '16 at 20:58
6
$\begingroup$

$\frac{2^n}{6^n}=(\frac{1}{3})^n$ and $\frac{3^n}{6^n}=(\frac{1}{2})^n$

Now, use the well known result that for $|x|<1$,

$$\sum \limits_{n=0}^{\infty}x^n=\frac{1}{1-x}$$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

Note that the sum $\sum_{n=0}^{\infty}r^{n}=\frac{1}{1-r}$ for $|r|<1$. According to this fact $\sum_{n=0}^{\infty}\frac{2^{n}+3^{n}}{6^{n}}=\sum_{n=0}^{\infty}\frac{2^{n}}{6^{n}}+\sum_{n=0}^{\infty}\frac{3^{n}}{6^{n}}=\sum_{n=0}^{\infty}(\frac{2}{6})^{n}+\sum_{n=0}^{\infty}(\frac{3}{6})^{n}=\frac{1}{1-1/3}+\frac{1}{1-1/2}=\frac{7}{2}$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.